(untitled) (Research, Society and Development, 2021)
This article aimed to show the importance of preparation and regulation in the sphere of the Military Police of the State of Tocantins of the Standard Administrative Procedure (PAP). The work on screen, when put into practice, will provide standardization for the Tocantins’ military police who work in the administrative service. Furthermore, if this proposal is implemented, it will directly reflect on the excellence of the work provided to the population of Tocantins. Thus, this scientific work reached the conclusion that the PMTO needs to standardize its administrative procedures. In the methodological part, the research is descriptive, bibliographical, documental, exploratory and of an applied nature, carrying out a qualitative qualitative approach and using the deductive method. Finally, with the regulation of the aforementioned proposal, the company will have a better quality service provided and the members of the PMTO administrative service will boost productivity and, consequently, the institution will be further strengthened by preparing and implementing this standardization of administrative activities.